High-impermeability concrete suitable for fabricated pavement and preparation method of high-impermeability concrete

By using limestone calcined clay cement, polyethylene fiber and modified polymer components in prefabricated pavement concrete, the problem of insufficient permeability of prefabricated pavement is solved, and the effect of high permeability and high strength and high toughness is achieved.

CN119263707APending Publication Date: 2025-01-07CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411234276.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Prefabricated pavement is prone to water seepage problems during use, resulting in insufficient permeability and affecting its durability and mechanical properties.

Method used

The use of limestone calcined clay cement, polyethylene fiber, silane modified polymer, acrylic copolymer and polyvinyl formaldehyde, and the use of LC3 cement, the bridging of fibers, the combination of water reducing agent and waterproofing agent is used to form a high level. Concrete with impermeability resistance.

Benefits of technology

It significantly improves the seepage resistance and durability of concrete, breaks the brittle damage characteristics of traditional concrete, provides high strength and high toughness, and is suitable for sustainable use of prefabricated pavements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263707A_ABST
    Figure CN119263707A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete materials, and particularly relates to high-impermeability concrete suitable for a fabricated pavement and a preparation method of the high-impermeability concrete. The high-impermeability concrete suitable for the fabricated pavement is prepared from the following raw materials in parts by weight: 360-550 parts of a cementing material, 300-360 parts of fine aggregate, 1-3 parts of a water reducing agent, 1-3 parts of a waterproof agent, 2-5 parts of polyethylene fibers, 120-160 parts of water and an impermeability component, wherein the cementing material is prepared from 110 to 180 parts of limestone calcined clay cement, 30 to 70 parts of silica fume and 220 to 300 parts of fly ash. The invention aims to prepare the concrete with high impermeability through the combined action of the LC3 cement, the PE fiber, the waterproof agent, the silane modified polymer, the acrylic copolymer and the polyvinyl formal, the concrete is suitable for the fabricated pavement, and the porosity is reduced and the impermeability of a cement base is improved by preparing the LC3 cement; the PE fibers are adopted, so that high-strength and high-toughness performance is provided; the water reducing agent and the waterproof agent are added, so that the compactness of the concrete material is improved, and the impermeability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of concrete materials, and in particular relates to a high-impermeability concrete suitable for assembled pavement and a preparation method thereof. Background Art

[0002] Prefabricated pavement technology refers to a type of technology that completes the prefabrication of the pavement structure layer in the factory, transports it to the construction site for assembly, joint treatment and other subsequent processes to complete the rapid construction of the pavement structure. Compared with traditional concrete pavements, the future development of prefabricated pavements tends to be mechanized and automated, using a complete set of mechanized equipment, from the prefabrication of the pavement system in the factory to the assembly operations corresponding to different application occasions.

[0003] The use of prefabricated pavements not only takes into account the bearing capacity, but also its durability, especially its impermeability. In the rainy season, there is often water accumulation on the road surface. The impermeability of the road surface is particularly important and is related to the sustainability of its use.

[0004] Concrete impermeability refers to the ability of concrete to resist water penetration. Water penetration refers to the process of water entering the interior of concrete through the pores and cracks of concrete. If the concrete does not have sufficient impermeability, moisture may cause corrosion of the concrete, rust of the steel bars, and gas or chemicals in the air to enter the interior of the concrete, thereby reducing the durability and mechanical properties of the concrete structure. However, the current concrete will crack due to external environmental factors (vehicle rolling, temperature, etc.) during long-term use, which makes it easy for water to seep into the interior, affecting the overall use effect of the concrete and needs to be improved.

[0005] Therefore, for the technical field of this invention, how to provide a new structure of high-permeability concrete suitable for prefabricated pavements and a preparation method thereof to solve or improve at least one of the above-mentioned technical problems has a relatively practical significance. Summary of the invention

[0006] The object of the present invention is to provide a new structure of high-impermeability concrete suitable for assembled pavements and a preparation method thereof, so as to solve or improve at least one technical problem existing in the related art.

[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0008] A high-impermeability concrete suitable for assembled pavement is prepared from the following raw materials in parts by weight: 360-550 parts of cementitious materials, 300-360 parts of fine aggregate, 1-3 parts of water reducer, 1-3 parts of waterproofing agent, 2-5 parts of polyethylene fiber, 120-160 parts of water, and an impermeability component; wherein the cementitious materials include 110-180 parts of limestone calcined clay cement, 30-70 parts of silica fume, and 220-300 parts of fly ash; and the impermeability component includes 1-3 parts of silane-modified polymer and 1-3 parts of polyvinyl formal; or, 1-3 parts of silane-modified polymer and 1-3 parts of acrylic copolymer; or, 1-3 parts of acrylic copolymer and 1-3 parts of polyvinyl formal; or, 1-3 parts of silane-modified polymer, 1-3 parts of acrylic copolymer, and 1-3 parts of polyvinyl formal.

[0009] As an improvement on the above-mentioned high-impermeability concrete suitable for assembled pavement, the water reducer is a polycarboxylic acid high-efficiency water reducer, and the water reduction rate of the polycarboxylic acid high-efficiency water reducer is greater than 20%.

[0010] As an improvement on the above-mentioned high-impermeability concrete suitable for assembled pavements, the waterproofing agent is a sodium silicate waterproofing agent.

[0011] As an improvement on the above-mentioned high-impermeability concrete suitable for assembled pavements, the limestone calcined clay cement is prepared by mixing cement clinker, limestone, gypsum and kaolin calcined clay.

[0012] As an improvement on the above-mentioned high-impermeability concrete suitable for assembled pavements, the polyethylene fiber has a diameter of 24 μm, a length of 12 mm, a density of 0.98 g / cm3, and a volume fraction of 2%.

[0013] As an improvement on the above-mentioned high-impermeability concrete suitable for prefabricated pavements, the fly ash is low-calcium fly ash.

[0014] As an improvement on the above-mentioned high-impermeability concrete suitable for prefabricated pavements, the silica fume is highly active micro silica fume.

[0015] As an improvement on the above-mentioned high-impermeability concrete suitable for assembled pavements, the fine aggregate is quartz sand with a size of 160-200 μm.

[0016] As an improvement on the above-mentioned high-impermeability concrete suitable for prefabricated pavements, the water is ordinary tap water, and / or the silane-modified polymer is silane-modified polyurethane; and / or the acrylic copolymer is acrylic-butadiene copolymer.

[0017] The purpose of the present invention is to prepare a concrete with high impermeability by using LC3 cement, PE fiber, waterproofing agent, silane modified polymer, acrylic copolymer, and polyvinyl formal, which is suitable for assembled pavements. The high impermeability concrete suitable for assembled pavements of the present invention has the following technical effects: 1. The cement used is limestone calcined clay cement, which is prepared by mixing cement clinker, limestone, gypsum, and calcined clay. The volcanic ash reaction of the calcined clay reduces the porosity of the LC3 cement and improves the density, which is beneficial to improving the waterproof performance of the concrete material. 2. The present invention uses PE fiber, and the bridging effect of the fiber can improve the strength, ductility, and toughness of ECC concrete, breaking the defects of traditional ordinary concrete that is prone to brittle failure and insufficient durability. At the same time, the random distribution of the fiber can reduce the loss rate of water and reduce the number of voids in the concrete, which is beneficial to improving the impermeability of the concrete material. At the same time, ECC still shows good impermeability in the cracked state, mainly due to its good crack control ability. The average crack width of ECC can be controlled below 100μm, and most of the ECC prepared now basically controls the crack width between 20-60μm, so the impermeability in the cracked state is also significantly better than ordinary concrete. 3. The addition of water reducer can reduce the amount of water, increase the density of concrete, and improve the impermeability; the addition of waterproofing agent can fill the voids inside the concrete, reduce the porosity, and improve the impermeability of concrete. 4. The concrete material of the present invention can provide high strength and high toughness while meeting the high impermeability performance, and is suitable for the sustainable use of prefabricated pavements. 5. Silane-modified polymers are hydrophobic and can form a hydrophobic film on the surface of cement-based materials, thereby reducing water penetration. The active functional groups of silane (such as amino, epoxy or others) will react with the hydroxyl (-OH) on the cement surface to form a siloxane (Si-O-Si) structure, which enhances the interfacial adhesion and thus improves the overall density and impermeability. Acrylic copolymers can form a continuous polymer film inside and on the surface of cement-based materials, which can block water penetration. The hydroxyl (-OH) in polyvinyl formal may react with the hydroxyl in the siloxane (Si-O-Si) network in the cement hydration product to form a more stable composite structure, enhancing the durability and impermeability of the material.

[0018] On the other hand, the present invention provides a method for preparing high-impermeability concrete suitable for assembled pavement, comprising the following steps: firstly dry-mix limestone calcined clay cement, fly ash, silica fume, fine aggregate, 2 / 3 of polyethylene fiber, waterproofing agent and 1:1:1 silane-modified polymer, acrylic copolymer and polyvinyl formal for 5 minutes, then add water and water-reducing agent and wet-mix for 5 minutes, and finally add 1 / 3 of polyethylene fiber and wet-mix for 6 minutes to prepare concrete material by mixing: pouring the formed concrete material into a mold, removing the mold for no less than 24 hours, and putting it into a steam curing box for steam curing to a specified age.

[0019] Since the above-mentioned method for preparing high-permeability concrete suitable for prefabricated pavements has the same inventive concept as the above-mentioned high-permeability concrete suitable for prefabricated pavements, the above-mentioned method for preparing high-permeability concrete suitable for prefabricated pavements has all the technical effects of the above-mentioned high-permeability concrete suitable for prefabricated pavements, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 The figure is a schematic flow chart of a method for preparing high-impermeability concrete suitable for assembled pavement according to one embodiment of the present invention. DETAILED DESCRIPTION

[0022] In the description of the present invention, it is to be understood that the terms “center”, “longitudinal”, “lateral”, “up”, “down”, “front”, “back”, “left”, “right”, “vertical”, “horizontal”, “top”, “bottom”, “inside”, “outside”, “axial”, “radial”, etc., indicating orientations or positional relationships are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0023] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.

[0024] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0025] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0026] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0027] The high impermeability concrete suitable for prefabricated pavement provided in an embodiment of the present invention is prepared from the following raw materials in parts by weight: 360-550 parts of cementitious materials, 300-360 parts of fine aggregate, 1-3 parts of water reducer, 1-3 parts of waterproofing agent, 2-5 parts of polyethylene fiber, 120-160 parts of water, and an impermeability component; wherein the cementitious materials include 110-180 parts of limestone calcined clay cement, 30-70 parts of silica fume, and 220-300 parts of fly ash, and the impermeability component includes 1-3 parts of silane-modified polymer and 1-3 parts of polyvinyl formal; or, 1-3 parts of silane-modified polymer and 1-3 parts of acrylic copolymer; or, 1-3 parts of acrylic copolymer and 1-3 parts of polyvinyl formal; or, 1-3 parts of silane-modified polymer, 1-3 parts of acrylic copolymer, and 1-3 parts of polyvinyl formal. Limestone calcined clay cement is prepared by mixing cement clinker, gypsum, limestone and kaolin calcined clay.

[0028] In some preferred embodiments of the present invention, the high impermeability concrete suitable for prefabricated pavement provided by the embodiments of the present invention is made from the following raw materials in parts by weight: 360-550 parts of cementitious material, 300-360 parts of fine aggregate, 1-3 parts of water reducer, 1-3 parts of waterproofing agent, 2-5 parts of polyethylene fiber, 120-160 parts of water, and an impermeability component; wherein the cementitious material includes 110-180 parts of limestone calcined clay cement, 30-70 parts of silica fume, and 220-300 parts of fly ash, and the impermeability component includes 1-3 parts of silane-modified polymer, 1-3 parts of acrylic copolymer, and 1-3 parts of polyvinyl formal, and the silane-modified polymer, acrylic copolymer, and polyvinyl formal are matched in a weight ratio of 1:1:1, such as the impermeability component includes 2 parts of silane-modified polymer, 2 parts of acrylic copolymer, and 2 parts of polyvinyl formal.

[0029] Most hydraulic cements are based on Portland cement. Cement produces carbon dioxide in the production process and in the energy plants that generate electricity by carrying out the production process. Therefore, the production of cement is the main source of carbon dioxide emissions today and one of the main causes of global warming. The LC3 cement (calcined limestone clay cement) used in the present invention refers to limestone and calcined kaolin clay replacing cement clinker in a certain proportion, and gypsum is added at the same time. It is a green low-carbon silicate cement. Compared with fly ash and ground slag, calcined clay minerals have higher volcanic ash activity, and when replacing part of silicate cement, it does not affect the early mechanical properties of cement-based materials. At the same time, the raw material kaolin of calcined clay is rich in resources, and low-temperature calcination does not produce carbon dioxide. Replacing part of silicate cement clinker not only reduces carbon emissions in the cement production process, but also maintains good mechanical properties. At the same time, the volcanic ash reaction of calcined clay makes the porosity of LC3 cement small and the structure dense, which can improve the impermeability of cement-based. Therefore, the use of LC3 cement can improve the impermeability of concrete materials and reduce carbon dioxide emissions.

[0030] Polyethylene fiber is also called PE fiber. The density of PE fiber is 0.98g / cm3 and the tensile strength can reach 3000MPa. The strength of high-strength and high-toughness concrete (ECC) with added fibers is much greater than that of ordinary concrete. Most notably, the tensile strain capacity of ECC can reach more than 2%, which is mainly due to the bridging effect of the fiber, which improves the cohesion between the cement matrix and the fiber. When subjected to external tensile loads, ECC concrete can produce many fine cracks, which play a role in dispersing stress, but the width of the cracks can often be controlled within 100μm, thereby greatly improving the ductility of the concrete. PE fibers are randomly distributed in concrete, which has an obstructive effect on the sinking of aggregates and the rise of water, reducing the water loss rate of concrete, thereby reducing the number of harmful pores with larger pore sizes in concrete, improving the density of concrete, reducing the pores of concrete, and thus improving the impermeability of concrete. Therefore, the use of PE fibers can not only improve the strength and toughness of concrete materials, but also improve the impermeability of concrete materials.

[0031] In some embodiments of the present invention, the water reducer used is a polycarboxylic acid high-efficiency water reducer, the water reduction rate of the polycarboxylic acid high-efficiency water reducer is greater than 20%, and the waterproofing agent used is a sodium silicate waterproofing agent. The hydrophobic group in the water reducer molecule can be directional adsorbed on the surface of cement particles, and the hydrophilic group faces the aqueous solution, forming a molecular adsorption film on the surface of cement particles, thereby reducing the cement-water interface energy, so that the surface of the cement particles carries the same charge, forming a repulsive force, and releasing the water wrapped in the flocculation structure formed after the cement is added with water, which plays an adsorption and dispersion role. The waterproofing agent uses its ability to swell into a colloid to form micropores during the solidification of cement, and gradually reduces the size and number of pores in the subsequent crystallization process, thereby achieving the purpose of waterproofing, having good water resistance, alkali resistance and weathering resistance, can effectively prevent the penetration of water molecules, and help protect the durability of cement structures. Therefore, a water reducer is used to improve the fluidity of concrete and meet the uniform dispersion of fibers; a waterproofing agent is used to improve the impermeability of concrete, reduce porosity, and increase density.

[0032] In some embodiments of the present invention, the silane-modified polymer used is silane-modified polyurethane, and the acrylic copolymer used is acrylic acid-butadiene copolymer.Silane-modified polymer has hydrophobicity, can form a layer of hydrophobic film on the surface of cement-based materials, thereby reducing the penetration of water, the active functional groups of silane (such as amino, epoxy or other) can react with the hydroxyl (-OH) on the cement surface to form siloxane (Si-O-Si) structure, this structure helps to enhance the adhesion between silane and cement substrate, enhances interfacial adhesion, thereby improves overall compactness and impermeability.Acrylic copolymer can form continuous polymer film inside and on the surface of cement-based materials, and this film can block the penetration of water.The hydroxyl (-OH) in polyvinyl formal may react with the hydroxyl in the siloxane (Si-O-Si) network in the cement hydration product to form a new chemical structure or cross-linked network, forming a more stable composite structure, reinforcing material durability and impermeability.

[0033] It should be noted that 1. PE fiber plays a bridging role, so that when concrete is subjected to tensile load, multiple cracks are generated to disperse stress, so that ECC concrete has good tensile strength, ductility, and toughness, breaking the defects of traditional ordinary concrete that is prone to brittle failure and insufficient durability. At the same time, the random distribution of fibers can reduce the rate of water loss and the number of voids in concrete, which is conducive to improving the impermeability of concrete materials. ECC has good self-healing properties, and the width of the cracks is usually less than 100μm. The cracks complete self-healing in a short time, which can reduce the intrusion of water and corrosive ions. Specifically, ECC still shows good impermeability in the cracked state, mainly due to its good crack control ability. The average crack width of ECC can be controlled below 100μm, and most of the ECCs prepared now basically control the crack width between 20-60μm, so the impermeability in the cracked state is also significantly better than ordinary concrete. 2. The permeable waterproofing agent can penetrate into the concrete and form a chemical reaction inside the concrete to fill the pores to fully improve the concrete's impermeability. In other words, the addition of the waterproofing agent can fill the voids inside the concrete, reduce the porosity, and improve the concrete's impermeability. 3. The water-reducing agent has a strong adsorption and dispersion effect on cement, which can reduce the amount of cement and the amount of water. The water-cement ratio is the main factor affecting the concrete's impermeability. Therefore, the less water is used, the smaller the water-cement ratio is, the higher the strength of the concrete is, the lower the porosity is, the density of the concrete is increased, and the concrete's impermeability is improved. In other words, the addition of the water-reducing agent can reduce the amount of water, increase the density of the concrete, and improve the impermeability of the concrete. 4. Calcined clay and limestone are used to replace part of the cement clinker, and gypsum is added to mix and prepare LC3 cement. Calcined clay (the main component includes activated alumina) and limestone can react in an alkaline environment to form a hydration product, hydrated calcium aluminate, thereby further reducing the material's porosity and improving the impermeability. 5. Silane-modified polymers can improve the density and impermeability of concrete, reduce water ingress, and improve the tensile strength and durability of concrete; acrylic copolymers can improve the bonding and tensile strength of concrete, reduce crack formation, enhance the impermeability of concrete, and prevent water ingress; polyvinyl formal can improve the bonding and tensile strength of concrete, reduce crack formation, enhance the impermeability of concrete, and prevent water ingress.

[0034] From the above content, it can be seen that the purpose of the present invention is to prepare a concrete with high impermeability by using LC3 cement, PE fiber, waterproofing agent, silane-modified polymer, acrylic copolymer, and polyvinyl formal, which is suitable for assembled pavement. The high impermeability concrete suitable for assembled pavement of the present invention has the following technical effects:

[0035] 1. The cement used is limestone calcined clay cement, which is prepared by mixing cement clinker, limestone, gypsum and calcined clay. The volcanic ash reaction of calcined clay reduces the porosity of LC3 cement and increases its density, which is beneficial to improving the waterproof performance of concrete materials.

[0036] 2. The present invention adopts PE fiber, and the bridging effect of the fiber can improve the strength, ductility and toughness of ECC concrete, breaking the defects of traditional ordinary concrete that is prone to brittle failure and insufficient durability. At the same time, the random distribution of the fiber can reduce the rate of water loss and the number of voids in the concrete, which is beneficial to improving the impermeability of the concrete material. At the same time, ECC still shows good impermeability in the cracked state, mainly due to its good crack control ability. The average crack width of ECC can be controlled below 100μm, and most of the ECC prepared now basically controls the crack width between 20-60μm, so the impermeability in the cracked state is also significantly better than that of ordinary concrete.

[0037] 3. The addition of water reducing agent can reduce the amount of water used, increase the density of concrete and improve its anti-seepage performance; the addition of waterproofing agent can fill the voids inside the concrete, reduce the porosity and improve the anti-seepage performance of concrete.

[0038] 4. The concrete material of the present invention can provide high strength and high toughness while meeting the requirements of high anti-permeability performance, and is suitable for sustainable use of prefabricated pavements.

[0039] 5. Silane-modified polymers are hydrophobic and can form a hydrophobic film on the surface of cement-based materials, thereby reducing water penetration. The active functional groups of silane (such as amino, epoxy or others) will react with the hydroxyl (-OH) on the cement surface to form a siloxane (Si-O-Si) structure, which enhances the interfacial adhesion and thus improves the overall density and impermeability. Acrylic copolymers can form a continuous polymer film inside and on the surface of cement-based materials, which can block water penetration. The hydroxyl (-OH) in polyvinyl formal may react with the hydroxyl in the siloxane (Si-O-Si) network in the cement hydration product to form a more stable composite structure, enhancing the durability and impermeability of the material.

[0040] like Figure 1As shown, the preparation method of high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention includes the following steps: firstly, limestone calcined clay cement, fly ash, silica fume, fine aggregate, 2 / 3 polyethylene fiber, waterproofing agent and 1:1:1 silane modified polymer, acrylic copolymer, polyvinyl alcohol formal are dry mixed for 5 minutes, then water and water reducing agent are added for wet mixing for 5 minutes, and finally 1 / 3 polyethylene fiber is added for wet mixing for 6 minutes. The concrete material is prepared by mixing: the formed concrete material is poured into a mold, the mold is removed for no less than 24 hours, and it is placed in a steam curing box for steam curing to the specified age.

[0041] In a specific embodiment 1 of the present invention, a method for preparing high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention comprises the following steps: (1) weighing the following raw materials by mass percentage: 80 parts of cement clinker, 24 parts of limestone, 8 parts of gypsum and 48 parts of kaolin calcined clay, mixing and stirring them evenly to prepare LC3 cement. (2) A concrete with good impermeability is composed of cement, fine aggregate, fly ash, silica fume, waterproofing agent, water reducing agent, silane modified polymer, acrylic copolymer, polyvinyl formal, PE fiber and water, and the specific gravity of each component is as follows: 160 parts of cement, 360 parts of quartz sand, 280 parts of fly ash, 60 parts of silica fume, 2 parts of water reducing agent, 3 parts of waterproofing agent, 2 parts of silane modified polymer, 2 parts of acrylic copolymer, 2 parts of polyvinyl formal, 2 parts of PE fiber and 120 parts of water. (3) Stir LC3 cement, quartz sand, fly ash, silica fume, waterproofing agent, PE fiber (2 / 3), silane-modified polymer, acrylic copolymer, and polyvinyl alcohol formal at low speed for 5 minutes to fully mix the materials. (4) Take ordinary tap water and water reducer, fully blend them, add them to the cement-based materials just stirred, and continue stirring for 6 minutes. Add the remaining 1 / 3 of the fiber and continue stirring for 5 minutes. (5) Pour the prepared concrete into the mold, remove the mold for no less than 24 hours, and then place it in a steam curing box for curing to the specified age, and take out the specimen for testing. (6) When cement meets water, the silicate components (3CaO·SiO2, 2CaO·SiO2) and aluminate components (3CaO·Al2O3) in the cement will combine with the hydroxide ions OH- in the water to react chemically to form calcium silicate gel and calcium aluminate gel. Fly ash particles are fine and contain a large amount of active SiO2 and Al2O3, while silica fume is not only fine but also contains more active SiO2. They will undergo secondary hydration reaction (volcanic ash reaction) with calcium hydroxide formed by cement hydration reaction to generate hydrated calcium silicate and hydrated calcium aluminate, which fill the gaps between cement particles, increase the density of concrete, reduce the porosity of concrete, and improve the impermeability of concrete. Quartz sand has a fine particle size and can fill the gaps in concrete materials and improve the compaction performance.

[0042] In the specific embodiment 2 of the present invention, the preparation method of high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention comprises the following steps: (1) weighing the following raw materials by mass percentage: 70 parts of cement clinker, 21 parts of limestone, 7 parts of gypsum and 42 parts of kaolin calcined clay, mixing and stirring to prepare LC3 cement. (2) A concrete with good impermeability is composed of cement, fine aggregate, fly ash, silica fume, waterproofing agent, water reducing agent, silane modified polymer, acrylic copolymer, PE fiber and water, and the specific gravity of each component is as follows: 160 parts of cement, 360 parts of quartz sand, 280 parts of fly ash, 60 parts of silica fume, 2 parts of water reducing agent, 3 parts of waterproofing agent, 2 parts of silane modified polymer, 2 parts of acrylic copolymer, 2 parts of PE fiber and 120 parts of water. (3) stirring LC3 cement, quartz sand, fly ash, silica fume, waterproofing agent, PE fiber (2 / 3), silane modified polymer and acrylic copolymer at low speed for 5 minutes to fully mix the materials. (4) Take ordinary tap water and water reducer, fully blend them, add them to the cement-based material just stirred, and continue stirring for 6 minutes. Add the remaining 1 / 3 of the fiber and continue stirring for 5 minutes. (5) Pour the prepared concrete into the mold, remove the mold for no less than 24 hours, and then place it in a steam curing box for curing to the specified age, and take out the specimen for testing. (6) When cement meets water, the silicate components (3CaO·SiO2, 2CaO·SiO2) and aluminate components (3CaO·Al2O3) in the cement will combine with the hydroxide ions OH- in the water to react chemically to form calcium silicate gel and calcium aluminate gel. Fly ash particles are fine and contain a large amount of active SiO2 and Al2O3, while silica fume is not only fine but also contains more active SiO2. They will undergo secondary hydration reaction (volcanic ash reaction) with calcium hydroxide formed by cement hydration reaction to generate hydrated calcium silicate and hydrated calcium aluminate, which fill the gaps between cement particles, increase the density of concrete, reduce the porosity of concrete, and improve the impermeability of concrete. Quartz sand has a fine particle size and can fill the gaps in concrete materials and improve the compaction performance.

[0043] In the specific embodiment 3 of the present invention, the preparation method of high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention comprises the following steps: (1) weighing the following raw materials by mass percentage: 80 parts of cement clinker, 24 parts of limestone, 8 parts of gypsum and 48 parts of kaolin calcined clay, mixing and stirring to prepare LC3 cement. (2) A concrete with good impermeability is composed of cement, fine aggregate, fly ash, silica fume, waterproofing agent, water reducing agent, acrylic copolymer, polyvinyl formal, PE fiber and water, and the specific gravity of each component is as follows: 160 parts of cement, 360 parts of quartz sand, 280 parts of fly ash, 60 parts of silica fume, 2 parts of water reducing agent, 3 parts of waterproofing agent, 2 parts of acrylic copolymer, 2 parts of polyvinyl formal, 2 parts of PE fiber and 120 parts of water. (3) stirring LC3 cement, quartz sand, fly ash, silica fume, waterproofing agent, PE fiber (2 / 3), acrylic copolymer and polyvinyl formal at low speed for 5 minutes to fully mix the materials. (4) Take ordinary tap water and water reducer, fully blend them, add them to the cement-based material just stirred, and continue stirring for 6 minutes. Add the remaining 1 / 3 of the fiber and continue stirring for 5 minutes. (5) Pour the prepared concrete into the mold, remove the mold for no less than 24 hours, and then place it in a steam curing box for curing to the specified age, and take out the specimen for testing. (6) When cement meets water, the silicate components (3CaO·SiO2, 2CaO·SiO2) and aluminate components (3CaO·Al2O3) in the cement will combine with the hydroxide ions OH- in the water to react chemically to form calcium silicate gel and calcium aluminate gel. Fly ash particles are fine and contain a large amount of active SiO2 and Al2O3, while silica fume is not only fine but also contains more active SiO2. They will undergo secondary hydration reaction (volcanic ash reaction) with calcium hydroxide formed by cement hydration reaction to generate hydrated calcium silicate and hydrated calcium aluminate, which fill the gaps between cement particles, increase the density of concrete, reduce the porosity of concrete, and improve the impermeability of concrete. Quartz sand has a fine particle size and can fill the gaps in concrete materials and improve the compaction performance.

[0044] In a specific embodiment 4 of the present invention, a method for preparing high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention comprises the following steps: (1) weighing the following raw materials by mass percentage: 80 parts of cement clinker, 24 parts of limestone, 8 parts of gypsum and 48 parts of kaolin calcined clay, mixing and stirring to prepare LC3 cement. (2) A concrete with good impermeability is composed of cement, fine aggregate, fly ash, silica fume, waterproofing agent, water reducing agent, silane modified polymer, polyvinyl alcohol formal, PE fiber and water, and the specific gravity of each component is as follows: 160 parts of cement, 360 parts of quartz sand, 280 parts of fly ash, 60 parts of silica fume, 2 parts of water reducing agent, 3 parts of waterproofing agent, 2 parts of silane modified polymer, 2 parts of polyvinyl alcohol formal, 2 parts of PE fiber and 120 parts of water. (3) Stir LC3 cement, quartz sand, fly ash, silica fume, waterproofing agent, PE fiber (2 / 3), silane-modified polymer, and polyvinyl alcohol formal at low speed for 5 minutes to fully mix the materials. (4) Take ordinary tap water and water reducer, fully blend them, add them to the cement-based materials just stirred, and continue stirring for 6 minutes. Add the remaining 1 / 3 of the fiber and continue stirring for 5 minutes. (5) Pour the prepared concrete into the mold, remove the mold for no less than 24 hours, and then place it in a steam curing box for curing to the specified age, and take out the specimen for testing. (6) When cement meets water, the silicate components (3CaO·SiO2, 2CaO·SiO2) and aluminate components (3CaO·Al2O3) in the cement will combine with the hydroxide ions OH- in the water to react chemically to form calcium silicate gel and calcium aluminate gel. Fly ash particles are fine and contain a large amount of active SiO2 and Al2O3, while silica fume is not only fine but also contains more active SiO2. They will undergo secondary hydration reaction (volcanic ash reaction) with calcium hydroxide formed by cement hydration reaction to generate hydrated calcium silicate and hydrated calcium aluminate, which fill the gaps between cement particles, increase the density of concrete, reduce the porosity of concrete, and improve the impermeability of concrete. Quartz sand has a fine particle size and can fill the gaps in concrete materials and improve the compaction performance.

[0045] In a specific embodiment 5 of the present invention, a method for preparing high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention comprises the following steps: (1) weighing the following raw materials by mass percentage: 80 parts of cement clinker, 24 parts of limestone, 8 parts of gypsum and 48 parts of kaolin calcined clay, mixing and stirring to prepare LC3 cement. (2) A concrete with good impermeability is composed of cement, fine aggregate, fly ash, silica fume, waterproofing agent, water reducing agent, silane modified polymer, acrylic copolymer, polyvinyl formal, PE fiber and water, and the specific gravity of each component is as follows: 160 parts of cement, 360 parts of quartz sand, 280 parts of fly ash, 60 parts of silica fume, 2 parts of water reducing agent, 3 parts of waterproofing agent, 1 part of silane modified polymer, 1 part of acrylic copolymer, 2 parts of polyvinyl formal, 2 parts of PE fiber and 120 parts of water. (3) Stir LC3 cement, quartz sand, fly ash, silica fume, waterproofing agent, PE fiber (2 / 3), silane-modified polymer, acrylic copolymer, and polyvinyl alcohol formal at low speed for 5 minutes to fully mix the materials. (4) Take ordinary tap water and water reducer, fully blend them, add them to the cement-based materials just stirred, and continue stirring for 6 minutes. Add the remaining 1 / 3 of the fiber and continue stirring for 5 minutes. (5) Pour the prepared concrete into the mold, remove the mold for no less than 24 hours, and then place it in a steam curing box for curing to the specified age, and take out the specimen for testing. (6) When cement meets water, the silicate components (3CaO·SiO2, 2CaO·SiO2) and aluminate components (3CaO·Al2O3) in the cement will combine with the hydroxide ions OH- in the water to react chemically to form calcium silicate gel and calcium aluminate gel. Fly ash particles are fine and contain a large amount of active SiO2 and Al2O3, while silica fume is not only fine but also contains more active SiO2. They will undergo secondary hydration reaction (volcanic ash reaction) with calcium hydroxide formed by cement hydration reaction to generate hydrated calcium silicate and hydrated calcium aluminate, which fill the gaps between cement particles, increase the density of concrete, reduce the porosity of concrete, and improve the impermeability of concrete. Quartz sand has a fine particle size and can fill the gaps in concrete materials and improve the compaction performance.

[0046] In a specific embodiment 6 of the present invention, a method for preparing high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention comprises the following steps: (1) weighing the following raw materials by mass percentage: 80 parts of cement clinker, 24 parts of limestone, 8 parts of gypsum and 48 parts of kaolin calcined clay, mixing and stirring to prepare LC3 cement. (2) A concrete with good impermeability is composed of cement, fine aggregate, fly ash, silica fume, waterproofing agent, water reducing agent, silane modified polymer, acrylic copolymer, polyvinyl formal, PE fiber and water, and the specific gravity of each component is as follows: 160 parts of cement, 360 parts of quartz sand, 280 parts of fly ash, 60 parts of silica fume, 2 parts of water reducing agent, 3 parts of waterproofing agent, 1 part of silane modified polymer, 2 parts of acrylic copolymer, 1 part of polyvinyl formal, 2 parts of PE fiber and 120 parts of water. (3) Stir LC3 cement, quartz sand, fly ash, silica fume, waterproofing agent, PE fiber (2 / 3), silane-modified polymer, acrylic copolymer, and polyvinyl alcohol formal at low speed for 5 minutes to fully mix the materials. (4) Take ordinary tap water and water reducer, fully blend them, add them to the cement-based materials just stirred, and continue stirring for 6 minutes. Add the remaining 1 / 3 of the fiber and continue stirring for 5 minutes. (5) Pour the prepared concrete into the mold, remove the mold for no less than 24 hours, and then place it in a steam curing box for curing to the specified age, and take out the specimen for testing. (6) When cement meets water, the silicate components (3CaO·SiO2, 2CaO·SiO2) and aluminate components (3CaO·Al2O3) in the cement will combine with the hydroxide ions OH- in the water to react chemically to form calcium silicate gel and calcium aluminate gel. Fly ash particles are fine and contain a large amount of active SiO2 and Al2O3, while silica fume is not only fine but also contains more active SiO2. They will undergo secondary hydration reaction (volcanic ash reaction) with calcium hydroxide formed by cement hydration reaction to generate hydrated calcium silicate and hydrated calcium aluminate, which fill the gaps between cement particles, increase the density of concrete, reduce the porosity of concrete, and improve the impermeability of concrete. Quartz sand has a fine particle size and can fill the gaps in concrete materials and improve the compaction performance.

[0047] In a specific embodiment 7 of the present invention, a method for preparing high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention comprises the following steps: (1) weighing the following raw materials by mass percentage: 80 parts of cement clinker, 24 parts of limestone, 8 parts of gypsum and 48 parts of kaolin calcined clay, mixing and stirring them evenly to prepare LC3 cement. (2) A concrete with good impermeability is composed of cement, fine aggregate, fly ash, silica fume, waterproofing agent, water reducing agent, silane modified polymer, acrylic copolymer, polyvinyl formal, PE fiber and water, and the specific gravity of each component is as follows: 160 parts of cement, 360 parts of quartz sand, 280 parts of fly ash, 60 parts of silica fume, 2 parts of water reducing agent, 3 parts of waterproofing agent, 2 parts of silane modified polymer, 1 part of acrylic copolymer, 1 part of polyvinyl formal, 2 parts of PE fiber and 120 parts of water. (3) Stir LC3 cement, quartz sand, fly ash, silica fume, waterproofing agent, PE fiber (2 / 3), silane-modified polymer, acrylic copolymer, and polyvinyl alcohol formal at low speed for 5 minutes to fully mix the materials. (4) Take ordinary tap water and water reducer, fully blend them, add them to the cement-based materials just stirred, and continue stirring for 6 minutes. Add the remaining 1 / 3 of the fiber and continue stirring for 5 minutes. (5) Pour the prepared concrete into the mold, remove the mold for no less than 24 hours, and then place it in a steam curing box for curing to the specified age, and take out the specimen for testing. (6) When cement meets water, the silicate components (3CaO·SiO2, 2CaO·SiO2) and aluminate components (3CaO·Al2O3) in the cement will combine with the hydroxide ions OH- in the water to react chemically to form calcium silicate gel and calcium aluminate gel. Fly ash particles are fine and contain a large amount of active SiO2 and Al2O3, while silica fume is not only fine but also contains more active SiO2. They will undergo secondary hydration reaction (volcanic ash reaction) with calcium hydroxide formed by cement hydration reaction to generate hydrated calcium silicate and hydrated calcium aluminate, which fill the gaps between cement particles, increase the density of concrete, reduce the porosity of concrete, and improve the impermeability of concrete. Quartz sand has a fine particle size and can fill the gaps in concrete materials and improve the compaction performance.

[0048] In the specific embodiment 8 of the present invention, the preparation method of high impermeability concrete suitable for assembled pavement provided by the embodiment of the present invention comprises the following steps: (1) weighing the following raw materials by mass percentage: 80 parts of cement clinker, 24 parts of limestone, 8 parts of gypsum and 48 parts of kaolin calcined clay, mixing and stirring evenly to prepare LC3 cement. (2) A concrete with good impermeability is composed of cement, fine aggregate, fly ash, silica fume, waterproofing agent, water reducing agent, PE fiber and water, and the specific gravity of each component is as follows: 160 parts of cement, 360 parts of quartz sand, 280 parts of fly ash, 60 parts of silica fume, 2 parts of water reducing agent, 3 parts of waterproofing agent, 2 parts of PE fiber and 120 parts of water. (3) stirring LC3 cement, quartz sand, fly ash, silica fume, waterproofing agent and PE fiber (2 / 3) at a low speed for 5 minutes to fully mix the materials. (4) taking ordinary tap water and water reducing agent, fully blending, adding to the cement-based material just stirred, and continuing stirring for 6 minutes. Add the remaining 1 / 3 of the fiber and continue stirring for 5 minutes. (5) Pour the prepared concrete into the mold, remove the mold for no less than 24 hours, and then place it in a steam curing box for curing until the specified age, and take out the test piece for testing. (6) When cement meets water, the silicate components (3CaO·SiO2, 2CaO·SiO2) and aluminate components (3CaO·Al2O3) in the cement will combine with the hydroxide ions OH- in the water to react chemically to form calcium silicate gel and calcium aluminate gel. Fly ash particles are fine and contain a large amount of active SiO2 and Al2O3, while silica ash is not only fine but also contains more active SiO2. They will undergo secondary hydration reaction (volcanic ash reaction) with calcium hydroxide formed by cement hydration reaction to generate hydrated calcium silicate and hydrated calcium aluminate, which fill the gaps between cement particles, increase the density of concrete, reduce the porosity of concrete, and improve the impermeability of concrete. Quartz sand has a fine particle size and can fill the voids in concrete materials to improve compaction performance.

[0049] The following table is the test results of specific embodiments 1-8:

[0050]

[0051] As can be seen from the above table, the compressive strength of specific embodiments 1-7 all reached 120 MPa, the ultimate tensile strain all reached more than 2% of the ECC tensile strain, and the permeability coefficient was relatively low, stable at 10 -10The impermeability is excellent and meets the requirements of prefabricated pavement, among which Example 1 has the best performance; Example 8 is a control group, so its performance is insufficient compared with other examples. The cement used in the present invention is LC3 cement calcined from cement clinker, limestone, gypsum and kaolin calcined clay. Compared with ordinary Portland cement, the volcanic ash reaction of calcined clay can effectively reduce the porosity and improve the impermeability of concrete materials; the fiber used is PE fiber, and the fiber bridging effect is conducive to improving the strength and toughness of concrete materials. At the same time, when the concrete is subjected to tensile load, the multiple cracks generated can be self-healed, so that the impermeability of concrete is restored, so that the concrete can be used sustainably; water reducer and waterproofing agent are added to improve the density of concrete materials and the impermeability, wherein the waterproofing agent is used to form micropores during the solidification of cement, and the size and number of pores are gradually reduced in the subsequent crystallization process, so as to achieve the purpose of waterproofing; silane-modified polymers, acrylic copolymers, and polyvinyl alcohol formal are added to control pores and enhance density to enhance impermeability. The concrete material of the present invention can provide high strength and high toughness while meeting the high impermeability performance, and is suitable for sustainable use of assembled pavements. In other words, the concrete of the present invention has the effect of improving the density of concrete, thereby improving the impermeability of concrete.

[0052] In summary, the high impermeability concrete suitable for prefabricated pavement of the present invention adopts a green low-carbon cement LC3 cement (limestone calcined clay cement), and its preparation raw materials include cement clinker, limestone, gypsum and kaolin calcined clay. In terms of mass percentage, the raw materials of the limestone calcined clay cement are: 40%-60% cement clinker, 10%-20% limestone, 4%-6% gypsum and 20%-40% kaolin calcined clay. LC3 cement has the advantages of rapid hydration, high early strength, dense pores, and effective resistance to the invasion of harmful media. The use of limestone and calcined clay to replace cement clinker at a high ratio can effectively reduce carbon emissions and improve impermeability. The fiber used is PE fiber, the fiber diameter is 24μm, the length is 12mm, the density is 0.98g / cm3, and the volume fraction of the fiber is 2%. The fly ash is low-calcium fly ash; the silica fume is highly active micro silica fume; the fine aggregate is quartz sand of 160-200 μm; the water reducer is polycarboxylic acid high-efficiency water reducer with a water reduction rate greater than 20%; the waterproofing agent is sodium silicate waterproofing agent; the water is ordinary tap water; the silane-modified polymer is silane-modified polyurethane; and the acrylic copolymer is acrylic acid-butadiene copolymer.

[0053] In the preparation method of high-impermeability concrete suitable for assembled pavement of the present invention, the materials are firstly dry-mixed at a low speed for 5 minutes to fully mix the materials, and 2 / 3 of the fibers are added to make the fibers evenly dispersed; then water and a water-reducing agent are added and wet-mixed for 5 minutes, the cement undergoes a hydration reaction, the fly ash and silica fume undergo a volcanic ash reaction, the fine aggregate fills the voids, the water-reducing agent reduces the interface energy between cement and water to form an adsorption and dispersion effect, the waterproofing agent forms micropores during the cement solidification process, and gradually reduces the size and number of the pores during the subsequent crystallization process, thereby achieving the purpose of waterproofing and fully integrating the fibers with the cement matrix; finally, 1 / 3 of the fibers are added and stirred for 6 minutes to fully stir the concrete materials. The capacity and slow stirring can meet the requirements of long PAM reaction time without destroying the flocs. Specifically, limestone calcined clay cement, fly ash, silica fume, fine aggregate, 2 / 3 polyethylene fiber, waterproofing agent, silane-modified polymer, acrylic copolymer, and polyvinyl formal in a ratio of 1:1:1 are dry-mixed for 5 minutes to make them uniform. The silane group can react with the silicate in the cement to form a cross-linked structure and enhance the density of the matrix. The functional groups in the acrylic copolymer may chemically react with certain components in the cement to form a cross-linked network, further improving the density of the material. The hydroxyl group (-OH) in the polyvinyl formal may react with the silicate in the cement hydration product to form a cross-linked network. The hydroxyl groups in the alkane (Si-O-Si) network react to form a cross-linked structure, which enhances the density of the material. Then, water and high-efficiency water-reducing agent are added and wet mixed for 5 minutes. The cement undergoes a hydration reaction, the fly ash and silica fume undergo a volcanic ash reaction, the fine aggregate fills the voids, the water-reducing agent reduces the interface energy between cement and water to form an adsorption and dispersion effect, and the waterproofing agent forms micro pores during the cement solidification process and gradually reduces the size and number of the pores during the subsequent crystallization process, thereby achieving the purpose of waterproofing and fully integrating the fiber with the cement matrix. Finally, 1 / 3 of the fiber is added and stirred for 6 minutes to fully mix the concrete material.

[0054] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0055] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high impermeability concrete suitable for assembled pavement, characterized by: The invention is prepared from the following raw materials in parts by weight: 360-550 parts of cementitious materials, 300-360 parts of fine aggregate, 1-3 parts of water reducing agent, 1-3 parts of waterproofing agent, 2-5 parts of polyethylene fiber, 120-160 parts of water and anti-seepage components; wherein the cementitious materials include 110-180 parts of limestone calcined clay cement, 30-70 parts of silica fume and 220-300 parts of fly ash; and the anti-seepage components include 1-3 parts of silane-modified polymer and 1-3 parts of polyvinyl formal; or, 1-3 parts of silane-modified polymer and 1-3 parts of acrylic copolymer; or, 1-3 parts of acrylic copolymer and 1-3 parts of polyvinyl formal; or, 1-3 parts of silane-modified polymer, 1-3 parts of acrylic copolymer and 1-3 parts of polyvinyl formal.

2. The high impermeability concrete suitable for assembled pavement according to claim 1 is characterized in that: The water reducing agent is a polycarboxylic acid high-efficiency water reducing agent, and the water reducing rate of the polycarboxylic acid high-efficiency water reducing agent is greater than 20%.

3. The high impermeability concrete suitable for assembled pavement according to claim 1, characterized in that: The waterproofing agent is a sodium silicate waterproofing agent.

4. The high impermeability concrete suitable for assembled pavement according to claim 1, characterized in that: The limestone calcined clay cement is prepared by mixing cement clinker, limestone, gypsum and kaolin calcined clay.

5. The high impermeability concrete suitable for assembled pavement according to claim 1, characterized in that: The polyethylene fiber has a diameter of 24 μm, a length of 12 mm, a density of 0.98 g / cm 3 , and a volume fraction of 2%.

6. The high impermeability concrete suitable for assembled pavement according to claim 1, characterized in that: The fly ash is low-calcium fly ash.

7. The high impermeability concrete suitable for assembled pavement according to claim 1, characterized in that: The silica fume is highly active micro silica fume.

8. The high impermeability concrete suitable for assembled pavement according to any one of claims 1 to 7, characterized in that: The fine aggregate is quartz sand with a size of 160-200 μm.

9. The high impermeability concrete suitable for assembled pavement according to any one of claims 1 to 7, characterized in that: The water is ordinary tap water, and / or the silane-modified polymer is silane-modified polyurethane; and / or the acrylic copolymer is acrylic acid-butadiene copolymer.

10. A method for preparing high impermeability concrete suitable for assembled pavement according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: firstly, limestone calcined clay cement, fly ash, silica fume, fine aggregate, 2 / 3 polyethylene fiber, waterproofing agent and 1:1:1 silane modified polymer, acrylic copolymer and polyvinyl formal are dry-mixed for 5 minutes, then water and water reducing agent are added and wet-mixed for 5 minutes, and finally 1 / 3 polyethylene fiber is added and wet-mixed for 6 minutes to prepare concrete material by mixing: the formed concrete material is poured into a mold, the mold is removed after not less than 24 hours, and the concrete material is put into a steam curing box and steam-cured to a specified age.

Citation Information

Cited By

  • Preparation method of ultrasonically dispersed silica fume reinforced LC3 cement-based material

    CN121850572A